Role of Birth Companions in Influencing Labor Duration on Partus Mother - Narmin, Narmin; Sakti, Putri Mulia; Kusika, Sri Yanti (Poltekkes Kemenkes Palu, 2025)
Introduction: The maternal mortality rate in Indonesia remained high at approximately 7,389 deaths in 2021, attributed to several factors. One significant factor was prolonged labor caused by uterine contraction abnormalities due to disrupted oxytocin hormone secretion resulting from increased stress responses, thereby highlighting the importance of the presence of a birth companion. Objective: This research aimed to know the influence of birth companions on labor duration. Methods: This study employed a cross-sectional design and was conducted within the working area of the Public Health Center in Palu City, Central Sulawesi, from January to June 2024. The sample comprised 50 postpartum mothers. Data were collected using observation sheets, processed using SPSS, and analyzed with the Chi-square test. Results: The results indicated no significant relationship between the mother's choice of birth companion and the duration of labor, with a p-value > 0.05 (p-value = 0.642). However, 60% of mothers in labor chose their husband as their birth companion. Conclusion: There was no significant relationship found in this study's variables due to the limited knowledge possessed by birth attendants, which resulted in suboptimal task performance. It is recommended that future researchers conduct studies focusing on improving the knowledge of birth attendants or exploring other variables that influence labor progress.